Preoperative PET-CT is useful for predicting recurrent extrahepatic metastasis of hepatocellular carcinoma after resection. Issue 124 (March 2020) - Morio, Kei; Kawaoka, Tomokazu; Aikata, Hiroshi; Namba, Maiko; Uchikawa, Shinsuke; Kodama, Kenichiro; Ohya, Kazuki; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; Yamauchi, Masami; Tsuge, Masataka; et al.
Highlights: 18 F-FDG PET-CT is good predictor of extrahepatic metastasis recurrence after surgery. 18 F-FDG PET-CT predicts extrahepatic metastasis recurrence with high sensitivity. 18 F-FDG PET-CT can predict extrahepatic metastasis recurrence before surgery. Abstract: Purpose: In recent years, it has been reported that use of 18 F-FDG PET-CT can reveal the degree of hepatocellular carcinoma malignancy. We evaluate the ability of a preoperative 18 F-FDG PET-CT to predict the recurrence of extrahepatic metastasis of HCC after surgery. Methods: We retrospectively examined 67 patients who received 18 F-FDG PET-CT prior to curative hepatic resection for HCC between April 2010 and March 2016. Multivariate Cox regression analysis was performed to identify the factors associated with recurrence of extrahepatic metastasis of HCC after surgery. We also evaluated the sensitivity, specifity, positive predictive value, negative predictive value and accuracy of diagnosis of 18 F-FDG PET-CT for recurrent extrahepatic metastasis of HCC after surgery. Results: The multivariate analysis identified a tumor-to-normal liver standardized uptake value ratio (TNR) ≥ 1.53 (hazard ratio [HR], 0.037; P = 0.003), multiple tumor nodules (HR, 0.121; P = 0.007), and presence of microvascular invasion (HR, 0.094; P = 0.003) as independent predictors of distant metastasis recurrence. A TNR ≥ 1.53 showed a sensitivity of 91.7 %, specificity of 76.4 %, positive predictive value of 45.8 %, negative predictive value of 97.7 %, and accuracy of 79.1 % for diagnosing distant metastasis recurrence of HCC. In a binomial logistic regression analysis of tumor factors associated with a TNR ≥ 1.53, poor tumor differentiation and large tumor size were significant factors. Conclusion: 18 F-FDG PET-CT and microvascular invasion may be useful for predicting the recurrence of extrahepatic metastasis of HCC after surgery.